ANALISIS KINERJA RETRIBUSI PASAR DALAM MENINGKATKAN PENDAPATAN PERUSAHAAN DAERAH PASAR UNIT PASAR SERIRIT KABUPATEN BULELENG - Putri Anggreni (STIMI Handayani Denpasar, 2016)
Retribution is one kind of market revenue sources region. Regions that areimportant to the Company Seririt Market Unit. This was proven during the period2009-2013 levy revenue realization fluktuatives market experience and indicatingthere are problems in the performance of the market in the company’s acceptance ofretribution Regional Market Unit Seririt. This study aimed to calculate the level ofeffectiveness and contribution levy market, and formulate appropriate strategies toimprove the performance of the market in the company’s acceptance of retributionRegional Market Unit Seririt. Based on the analysis that has been done can beconcluded that the implementation of market levies in Buleleng is the authority andresponsibility of the Regional Corporate Markets Buleleng and fully implemented byRegional Company Seririt Market Unit using the official assessment system, votingbased on Local Regulation, 4 in 2009 the collection system directly using valuableobjects or ticket, levy implementation market in the last five years running properly.Effectiveness achievement and contributions levy market Regional CorporateMarket Unit Seririt period 2009-2013 experienced fluctuate. So in need of properstrategy to increase market levies in Regional Corporate Market Unit Seririt namelyto socialize, improve infrastructure services market and increased scrutiny.